Diagnostic Imaging Dilemma of a Clival Lesion and Its Clinical Management Implications - Yuh, Sung-Joo; Woulfe, John; Corsten, Martin J.; Carrau, Ricardo L.; Prevedello, Daniel M.; Kassam, Amin B. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Background A retroclival lesion can represent a notochordal remnant–derived mass. The differential diagnoses includes benign lesions such as ecchordosis physaliphora (EP) and neuroenteric cyst or malignant ones such as chordomas. In the case of EP and chordoma, although both types arise from remnants of fetal notochord tissues, they represent two separate entities with different radiographic and biologic behaviors.Case Description We present a case of an incidental finding of a retroclival lesion. The magnetic resonance imaging (MRI) characteristics of the lesion match the neuroimaging profile of a benign lesion and are suggestive of an EP. There was no enhancement noted with the addition of gadolinium. Nonetheless, pathology determined the lesion to be a malignant chordoma.Conclusion The differential diagnosis of a retroclival lesion includes benign and malignant notochordal lesions. Here we present a case of a patient with an incidental finding of a retroclival lesion. Radiographic findings were suggestive of a benign lesion, possibly EP, yet the pathology revealed a chordoma. This report suggests that despite benign imaging, chordoma cannot be excluded and the implications for treatment can be significant. It is important to achieve the correct diagnosis because the prognostic and therapeutic implications are different.
Keywords: ecchordosis physaliphora; neuroenteric cyst; chordoma; benign; malignant; gadolinium; enhancement